A gastrointestinal stromal tumor of the jejunum presenting with an intratumoral abscess: A case report and a literature review. (2018) - Ito, Soichi; Tsuchitani, Yuma; Kim, Yuro; Hashimoto, Souhei; Miura, Yuichi; Uemura, Takuji; Katsura, Kazunori; Abe, Takayuki; Sato, Koichiro; Kato, Hirotaka
Highlights: An abscess with a thick and vascularized wall suggests an intratumoral abscess. GISTs developing into intratumoral abscesses are extremely rare. These GISTs often accompany tumor perforation and peritonitis. Careful handling is eligible in surgery for these GISTs. Administration of Imatinib mesylate should be considered for these GISTs. Abstract: Introduction: Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal tract. The small intestine is the second-most frequent location where GISTs occur after the stomach. Attention should be paid to small intestinal GISTs because they infrequently present with acute abdomen, which necessitates emergency surgery. This report describes a patient with a small intestinal GIST developing a giant intratumoral abscess, in whom emergency surgery was performed. Presentation of case: A 56-year-old woman presented with worsening abdominal pain. Computed tomography scan showed an approximately 9.5 cm × 9 cm tumor bearing a thick and hypervascularized wall with an internal air-fluid level. Emergency laparotomy revealed the tumor originated from the jejunum, and partial resection of the jejunum was performed. A large amount of pus was contained inside the tumor. Immunohistochemically, the tumor was diagnosed as a high risk GIST of the Cjejunum, and imatinib mesylate was initiated. Discussion and conclusion: When an intratumoral abscess in the abdomen is confirmed, GISTs should be listed as differential diagnosis. Complete surgical resetcion with careful handling and adjuvant chemotherapy with imatinib mesylate are considered to be important for this state.